AL-QUR’AN DI MATA AHLUL BAIT: Studi Pemikiran Hasyim al-Mousawi dalam Buku Al-Qur’an fi Madrasati Ahlil bait - Kholaf Al Muntadar; Abdul Azis (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract After the Prophet's and the Companions' absence, subsequent generations tried to interpret the Qur'an. That led to the emergence of various methods, tendencies, and understandings. However, it is important to note that the Qur'an being interpreted is the same. Differences in interpretation only became apparent when Muslims faced the complexity of problems that arose with the growth of Islamic civilisation. This research aims to discuss two topics: firstly, the epistemology of Shia interpretation, and secondly, Hashim al-Mousawi's perspective on the Qur'an in the book 'Al-Qur'an fi Madrasati Ahlil Bait.' This research aims to answer two formulations: Firstly, What is the epistemology of Shia interpretation? Secondly, How is Hashim al-Mousawi's perspective on the Qur'an in the book 'Al-Qur'an fi Madrasati Ahlil Bait'? Meanwhile, the study aims, first, to uncover Hasyim Al-Mousawi's views on the existence of the Qur'an in the book mentioned above. The second is to identify the advantages and disadvantages of Hasyim Al-Mousawi's analysis in the book when examining the Qur'an. As the data to be analysed is literary, this research will be conducted using a non-interactive approach, in which data will be collected through document analysis of library materials. Furthermore, by analysing the thoughts of Hashim Al-Mousawi, a Shia scholar, we can observe his method of thought and any inconsistencies or biases in his defence of the imams of Ahlu Bait when interpreting the Qur'an. The research concludes that Shia is heavily influenced by a model of interpretation based on intuition, commonly known as irfani. Secondly, Hashim Al-Mousawi is meticulous in using riwayah, clearly identifying them to ensure their accountability as supporting evidence. Keywords: Tafsir, Shia, Ahlul Bayt